Strategic planning and measuring government performance in Algeria: A study from the perspective of public policy analysis - Djamai, Yassine (The International tax journal, 2026)
This study aims to clarify the foundations on which the Algerian strategic plans are based and to show the extent of their success in achieving management of the political crisis that Algeria has known, and what are the mechanisms adopted to manage it at various levels. It will be explained how strategic planning has an important role in giving successful government performance by analyzing the general policy in Algeria, and all the factors and elements that helped to manage it in a logical and rational manner and in a good management manner, in a way that serves the public interests of the state and the private interests of individuals, while enjoying With some important rules and methods in management, oversight, and giving legal and human character to strategies for dealing with various crises, especially the political crisis, in effective ways that allow achieving goals that serve the state's public policy, and guarantee the citizen a strong safety that preserves the course of life in strong and easy ways, in addition to legislation that is in line with recognized values. within the social system.